The Thermodynamics of Medial Vascular Calcification - Millán, Ángel; Lanzer, Peter; Sorribas, Víctor (Frontiers in Cell and Developmental Biology, 2021)
Medial vascular calcification (MVC) is a degenerative process that involves the deposition of calcium in the arteries, with a high prevalence in chronic kidney disease (CKD), diabetes, and aging. Calcification is the process of precipitation largely of calcium phosphate, governed by the laws of thermodynamics that should be acknowledged in studies of this disease. Amorphous calcium phosphate (ACP) is the key constituent of early calcifications, mainly composed of Ca2+ and PO43– ions, which over time transform into hydroxyapatite (HAP) crystals. The supersaturation of ACP related to Ca2+ and PO43– activities establishes the risk of MVC, which can be modulated by the presence of promoter and inhibitor biomolecules. According to the thermodynamic parameters, the process of MVC implies: (i) an increase in Ca2+ and PO43– activities (rather than concentrations) exceeding the solubility product at the precipitating sites in the media; (ii) focally impaired equilibrium between promoter and inhibitor biomolecules; and (iii) the progression of HAP crystallization associated with nominal irreversibility of the process, even when the levels of Ca2+ and PO43– ions return to normal. Thus, physical-chemical processes in the media are fundamental to understanding MVC and represent the most critical factor for treatments’ considerations. Any pathogenetical proposal must therefore comply with the laws of thermodynamics and their expression within the medial layer.